THE INTERACTIVE ROLE OF MARKETING INTEGRITY IN ENHANCING BRAND INFLUENCE ON MARKETING SUCCESS - Assist Prof. Dr. Raad A. Raouf (Scholar Express Journals, 2022)
Organizations marketing their products is now only a small part of their ambitions extending towards excellence and marketing leadership. These cannot be achieved unless they succeed in establishing their brand in the mind of the customer because the focus of the work of these organizations create an effective relationship with him/her through the adoption of integrity in the organization’s dealings in general and in marketing activity in particular and through full disclosure of all facts related to the organization's products. In order to explain the logical relationship among these three variables (marketing success, brand, marketing integrity), the study adopted the questions expressing its problem as follows: 1- What are the most effective brand dimensions in promoting marketing success? 2- To what extent does marketing integrity contribute to promoting marketing success? 3- What is the impact of the brand in promoting marketing success through marketing integrity in the company's field of research? The importance of the research is evident in handling the three variables characterized by modernity, as well as their effective importance in the field under study. The research seeks to test the possibility of employing marketing integrity as an approach to improve the relationship between brand and marketing success.
Keywords: Marketing; Integrity; Brand; Marketing Success